2014
DOI: 10.1063/1.4887571
|View full text |Cite
|
Sign up to set email alerts
|

An explicit two-step rational method for the numerical solution of first order initial value problem

Abstract: Numerical solution of second order boundary value problem using rational method AIP Conference Proceedings 1682, 020013 (2015) Abstract. An explicit two-step, second order rational method for the numerical solution of first order initial value problems is introduced in this paper. Existing rational multistep methods required the computations of higher derivatives from a given initial value problem. However, the new two-step rational method does not require any computation of these higher derivatives, and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Such approaches have stronger stability properties as well. Some non-linear or one-step rational schemes in [16,17] or two-step in [18] are applicable for stiff and singular types of non-linear initial value problems. These schemes deal with the singularities at a pole at a given time interval with a low computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches have stronger stability properties as well. Some non-linear or one-step rational schemes in [16,17] or two-step in [18] are applicable for stiff and singular types of non-linear initial value problems. These schemes deal with the singularities at a pole at a given time interval with a low computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, it was shown that their method possesses better approximation, more efficient and needs shorter execution time than the Taylor method. Ying et al [4] considered…”
Section: Introductionmentioning
confidence: 99%
“…Such problems are found in the modeling of disease outbreak, war, radioactive decay, di¤usion process in biology and chemical reactions. Several scholars have developed exponentially …tted methods are the best methods for (1:1) among them are [1][2][3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%